Preliminary Analysis of Waste Water from Soyabean Oil Factory - Kataria, H.C. (Asian Journal of Chemistry, 2010)
The physico-chemical parameters of waste water of various manufacturing processes of edible oil (soyabean) industries of Pipariya (Hoshangabad) and Gadarwara (Narsinghpur) districts of Madhya Pradesh are analysed. The pollution parameters as pH, BOD, COD, TSS, oil and TDS have been observed in year 1998-99 for soyabean oil and other oilseeds. The flow variations and average flow pattern has also been noticed.